Detection of Listeria monocytogenes in Soft-Cheese and Sweet Yogurt Produced Locally in Baghdad - AL-Shamary, Ali H.A.; H.Najim, Najim (The Iraqi Journal of Veterinary Medicine, 2009)
In order to investigate the presence of Listeria monocytogenes in soft cheese and sweet yogurt producedlocally, this study was done by random collection of samples from different areas in Baghdad province and itssurrounding from different animals (Cows and Buffalos) as 55 total samples (47 soft –cheese samples and 8sweet-yogurt samples) from October 2007 till January 2008 and processed according to standard protocols ofListeria monocytogenes .The results showed isolation of 6 isolates from 55 samples(10.9%) as 5 isolates from 47 soft – cheese samples(10.638%) and 1 isolated from 8 sweet yogurt samples (12.5%),these revealed significant differences (P≤0.05) inisolation percentages between Cows and Buffalos .Samples of raw –dairy products from local Buffaloes recordedhighest isolation percentage of Listeria monocytogenes as 73.5%(23.5% represented 4 isolates from 17 soft –cheese samples and 50% represented 1 isolate from 2 yogurt samples) highest percentage of isolation of Listeriamonocytogenes from soft cheese samples occurred in January (2008) as 18.2% (2 isolates from 11samples)especially from Buffalos in Al-Taji region as 33.4% (1 isolate from 3 samples ) while ,highest isolationpercentage of Listeria monocytogenes from yogurt occurred in December (2007)as 50%,1 isolate from 2 samplesespecially from Buffaloes at Al-Fadhyllea region.We concluded from this study by contamination of soft –cheese and sweet-yoghurt samples produced locallyin Baghdad by Listeria monocytogenes .